Negative plate, lithium ion battery, preparation method of lithium ion battery and power utilization device

By introducing ether-containing bonded polymers into the negative electrode sheet of the lithium-ion battery, a stable SEI film is formed, which solves the problem of battery interface film damage and gas production caused by transition metal ions, and improves the cycling performance and safety of the battery.

CN119447176APending Publication Date: 2025-02-14SHANGHAI RUIPU ENERGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411599858.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The catalytic activity of transition metal ions in lithium-ion batteries leads to the destruction of solid electrolyte interface masks and increased gas production, which in turn affects the cycling performance and safety of the battery.

Method used

By introducing ether-containing bond polymers into the solid electrolyte interface film of the negative electrode sheet, a new carbon-containing species is formed, which enhances the stability of the SEI film and reduces the deposition and gas production of transition metal ions.

Benefits of technology

It effectively improves the circulation performance and safety of lithium-ion batteries, extends the service life of the battery, and reduces safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128599440000101
    Figure BDA0005128599440000101
  • Figure BDA0005128599440000111
    Figure BDA0005128599440000111
  • Figure BDA0005128599440000131
    Figure BDA0005128599440000131
Patent Text Reader

Abstract

The invention relates to a negative plate, a lithium ion battery, a preparation method of the lithium ion battery and a power utilization device. The negative plate comprises a negative current collector; the negative electrode active material layer is arranged on the surface of at least one side of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material and a solid electrolyte interface film coated on the surface of the negative electrode active material, and the solid electrolyte interface film has at least two signal peaks between 282eV and 286eV based on a C1s spectrum of the surface measured by X-ray photoelectron spectroscopy, and there is at least one signal peak between 290 eV and 292 eV. The SEI film of the negative plate provided by the invention has a new carbon-containing species, and the carbon-containing species shows that a new signal peak is additionally formed between 282eV and 286eV. The negative plate with the characteristics can effectively reduce deposition of transition metal ions on the surface of the negative electrode, protect the negative electrode, reduce gas production and further improve the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet, a lithium ion battery, a preparation method thereof, and an electric device. Background Art

[0002] Lithium-ion batteries are widely used in mobile phones, computers, electric vehicles and other fields due to their advantages such as high energy density, wide operating temperature range, long cycle life and fast charging and discharging.

[0003] At present, the cathode materials of lithium-ion batteries are mostly selected from oxide lithium salts with variable valence transition metal ions (such as ternary cathode materials) or polyanion transition metal lithium salts (such as lithium iron phosphate and lithium manganese iron phosphate). The stability of these variable valence transition metal ions changes with the change of valence during the charge and discharge process, and some of them will dissolve into the electrolyte.

[0004] However, these transition metal ions often have catalytic activity, and their migration to the negative electrode surface will accelerate the destruction and decomposition of the solid electrolyte interface film (SEI film). On the one hand, the SEI film loses its protective effect on the negative electrode material, causing structural damage to the negative electrode material; on the other hand, CO is generated during the reaction. 2 , alkanes and other gases increase the internal pressure of the battery, creating a safety hazard and causing capacity decay. Summary of the invention

[0005] Based on this, it is necessary to provide a negative electrode sheet, a lithium-ion battery and its preparation method, and an electrical device to improve the stability of the solid electrolyte interface film, reduce the deposition of transition metal ions on the negative electrode surface, protect the negative electrode, reduce gas production, and improve the battery's cycle performance.

[0006] The first aspect of the present application provides a negative electrode sheet, which includes: a negative electrode collector; and a negative electrode active material layer, which is arranged on the surface of at least one side of the negative electrode collector, the negative electrode active material layer includes a negative electrode active material and a solid electrolyte interface film coated on the surface of the negative electrode active material, and the solid electrolyte interface film has at least 2 signal peaks between 282eV and 286eV in the C1s spectrum of the surface measured based on X-ray photoelectron spectroscopy, and at least 1 signal peak between 290eV and 292eV.

[0007] In some embodiments, the solid electrolyte interface film includes one or more reaction products of a chemical reaction between an ether bond-containing polymer and a transition metal ion.

[0008] In some embodiments, the ether bond-containing polymer includes one or more of polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.

[0009] In some embodiments, a C1s spectrum of the surface of the solid electrolyte interface membrane measured based on X-ray photoelectron spectroscopy has two signal peaks between 282eV and 286eV, the two signal peaks are a first peak and a second peak, the binding energy of the first peak is lower than the binding energy of the second peak, and the difference between the binding energy of the first peak and the binding energy of the second peak is ≤1eV.

[0010] In some embodiments, the binding energy of the first peak is 283.5 eV to 284.5 eV, and the binding energy of the second peak is 284.5 eV to 285.5 eV.

[0011] In some embodiments, the integrated area P of the first peak 1 and the integrated area P of the second peak 2 The ratio meets: 0.2 <P 1 / P 2 <1.

[0012] A second aspect of the present application provides a lithium-ion battery, which includes a positive electrode sheet, the negative electrode sheet provided in the first aspect above, and a separator.

[0013] The third aspect of the present application provides a method for preparing a lithium-ion battery, which comprises the following steps: mixing a negative electrode active material, an ether bond-containing polymer, a conductive agent and a binder to obtain a mixture, adding a solvent to obtain a negative electrode slurry; coating the negative electrode slurry on at least one side of the surface of the negative electrode collector, drying, to obtain a negative electrode sheet; assembling the positive electrode sheet, the negative electrode sheet and the separator by injection, forming, and obtaining a lithium-ion battery.

[0014] In some embodiments, the water content of the negative electrode sheet is <300 ppm.

[0015] In some embodiments, the mass percentage of the ether bond-containing polymer in the mixture is 0.3% to 0.9%.

[0016] A fourth aspect of the present application provides an electrical device, which includes the lithium-ion battery provided by the second aspect above, or the lithium-ion battery prepared by the preparation method provided by the third aspect above.

[0017] Compared with the traditional technology, this application has at least the following beneficial effects:

[0018] The negative electrode sheet was tested by X-ray photoelectron spectroscopy to obtain the C1s spectrum of the surface, with a signal peak between 290eV and 292eV and an existing signal peak between 282eV and 286eV as the reference peaks. Compared with the conventional technology, the present application provides a new carbon-containing species on the solid electrolyte interface film of the negative electrode sheet, which is manifested as an additional new signal peak between 282eV and 286eV. Experimental data show that the solid electrolyte interface film of the negative electrode sheet with the above characteristics has a high stability, can effectively reduce the deposition of transition metal ions on the negative electrode surface, protect the negative electrode, reduce gas production, and thus improve the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of a process for preparing a lithium-ion battery in one embodiment of the present application.

[0020] Figure 2 It is a comparison diagram of the C1s spectrum of the X-ray photoelectron spectrum of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0021] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0022] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0023] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0024] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0025] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0026] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0027] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0028] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0029] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0030] The first aspect of the present application provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is arranged on the surface of at least one side of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material and a solid electrolyte interface film coated on the surface of the negative electrode active material, and the solid electrolyte interface film has at least two signal peaks between 282eV and 286eV in the C1s spectrum of the surface measured based on X-ray photoelectron spectroscopy, and at least one signal peak between 290eV and 292eV.

[0031] The negative electrode sheet was tested by X-ray photoelectron spectroscopy to obtain the C1s spectrum of the surface, with a signal peak between 290eV and 292eV and an existing signal peak between 282eV and 286eV as the reference peaks. Compared with the conventional technology, the present application provides a new carbon-containing species on the solid electrolyte interface film of the negative electrode sheet, which is manifested as an additional new signal peak between 282eV and 286eV. Experimental data show that the solid electrolyte interface film of the negative electrode sheet with the above characteristics has a high stability, can effectively reduce the deposition of transition metal ions on the negative electrode surface, protect the negative electrode, reduce gas production, and thus improve the cycle performance of the battery.

[0032] It can be understood that the SEI film of the negative electrode sheet provided in the present application retains conventional carbon-containing species in traditional technology, such as carbon-containing species represented as carbonates in the range of 290eV to 292eV, etc., and therefore has a lithium ion transmission capacity equivalent to that of the lithium ion battery negative electrode in traditional technology.

[0033] In some embodiments, the solid electrolyte interface membrane has two signal peaks between 282eV and 286eV in the C1s spectrum of the surface measured based on X-ray photoelectron spectroscopy, the two signal peaks are the first peak and the second peak, the binding energy of the first peak is lower than the binding energy of the second peak, and the difference between the binding energy of the first peak and the binding energy of the second peak is ≤1eV. Taking the existing signal peak (i.e., the second peak) between 282eV and 286eV as the reference peak, the new carbon-containing species on the SEI membrane of the negative electrode provided in the present application is shown as having a binding energy lower than the second peak between 282eV and 286eV, and the difference between the binding energy and the binding energy of the second peak is ≤1eV, forming a new signal peak (i.e., the first peak). Specifically, the binding energy of the first peak is 283.5eV to 284.5eV, and the binding energy of the second peak is 284.5eV to 285.5eV.

[0034] Furthermore, the integrated area P of the first peak 1 and the integrated area P of the second peak 2 The ratio meets: 0.2 <P 1 / P 2 <1. Furthermore, the integrated area P of the first peak 1 and the integrated area P of the second peak 2 The ratio meets: 0.3 <P 1 / P 2 <1. The integrated area of ​​the first peak P 1 and the integrated area P of the second peak 2 When the ratio is within the above range, the effects of reducing transition metal ion deposition and improving cycle performance are particularly obvious.

[0035] In some embodiments, the SEI film includes one or more reaction products of a chemical reaction between at least one ether bond-containing polymer and a transition metal ion.

[0036] The applicant's speculation on the reaction mechanism is as follows:

[0037] The reaction product formed by the chemical reaction between the ether bond polymer and the transition metal ion is a new carbon-containing species, which is presumed to be a transition metal carbide, which is shown as a signal peak between 282eV and 286eV on the C1s spectrum of the XPS test. Specifically, the binding energy of the signal peak is 283.5eV to 284.5eV. The carbon-containing species itself contains transition metal ions and has high stability, so the SEI film formed will not be decomposed by the catalysis of the transition metal ions in the electrolyte. In addition, since one of the raw materials in the generation process is an ether bond polymer, the SEI film formed has the characteristics of high dispersion and complete coating on the surface of the negative electrode material, which can continuously prevent the destructive effect of transition metal ions on the SEI film.

[0038] It can be understood that when the formed SEI film has multiple transition metal carbides, since their corresponding signal peaks are very close, they still form one signal peak after peak fitting.

[0039] In some embodiments, the ether bond-containing polymer includes one or more of polyethylene glycol, polypropylene glycol and polytetrahydrofuran diol. The ether bond-containing polymer contains a COC structural unit, which can form a stable coordination structure with a transition metal ion during the chemical formation process and eventually be converted into a stable transition metal carbide.

[0040] A second aspect of the present application provides a lithium-ion battery, which includes a positive electrode sheet, the negative electrode sheet provided by the first aspect above, and a separator.

[0041] In the conventional technology, in the positive electrode material with variable valence transition metal ions, due to the existence of the Jan-Taylor effect, Mn 3+ The stability is poor and it is easy to dissolve. 3+ The destructive effect on the negative electrode is particularly obvious. Therefore, when the positive electrode material contains more Mn 3+ When the negative electrode is subjected to high temperature, higher requirements are placed on the stability of the SEI film on the negative electrode surface.

[0042] In some embodiments, the positive electrode sheet includes one or more of lithium iron manganese phosphate material, nickel cobalt manganese ternary material, nickel manganese spinel material, lithium manganese phosphate material and lithium manganate material. The negative electrode sheet provided in the present application has a particularly outstanding resistance to Mn ions and is particularly suitable for use in Mn 3+Therefore, when the positive electrode sheet includes the above positive electrode material, the cycle life of the battery can be greatly improved.

[0043] The third aspect of the present application provides a method for preparing a lithium ion battery, such as Figure 1 As shown, the preparation method comprises the following steps:

[0044] S1. Mix the negative electrode active material, the ether bond-containing polymer, the conductive agent and the binder to obtain a mixture, and add a solvent to prepare a negative electrode slurry.

[0045] S2. Coating the negative electrode slurry on at least one side of the negative electrode current collector and drying it to obtain a negative electrode sheet.

[0046] S3, assembling the positive electrode sheet, the negative electrode sheet and the separator, injecting liquid, and forming, to obtain a lithium-ion battery.

[0047] In some embodiments, the ether bond-containing polymer includes one or more of polyethylene glycol, polypropylene glycol and polytetrahydrofuran diol. The ether bond-containing polymer contains a COC structural unit, which can form a stable coordination structure with the transition metal ions dissolved into the electrolyte from the positive electrode during the formation process, and finally be converted into a stable transition metal carbide.

[0048] In some embodiments, the mass percentage of the ether bond-containing polymer in the mixture is 0.3% to 0.9%, including but not limited to 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, and 0.9%. Since the transition metal ions in the positive electrode will continue to dissolve into the electrolyte, the transition metal ions are excessive. Therefore, by controlling the amount of the ether bond-containing polymer, the species content of the transition metal carbide in the SEI film finally formed can be controlled. When the mass percentage of the ether bond-containing polymer in the mixture is within the above range, the effect of reducing the deposition of transition metal ions and improving the cycle performance is particularly obvious.

[0049] In some embodiments, the water content of the negative electrode sheet is <300ppm, including but not limited to 100ppm, 150ppm, 200ppm, and 250ppm. When the water content of the electrode sheet is too high, water molecules form hydrogen bonds with the COC structural units of the ether bond polymer, resulting in the COC structural units being unable to form a stable coordination structure with transition metal ions during the formation process, and unable to form transition metal carbides. Therefore, the water content of the negative electrode sheet within the above-mentioned water content range is conducive to the coordination of the ether bond polymer with the transition metal ions, thereby facilitating the formation of a protective SEI film on the surface of the negative electrode active material, reducing the deposition of transition metal ions, and improving the cycle performance of the battery.

[0050] In some embodiments, in step S1, an auxiliary agent is added and mixed together to form a mixture. The auxiliary agent may be a conductive auxiliary agent, a dispersing auxiliary agent or a bonding auxiliary agent, and is used to improve the performance of the negative electrode slurry.

[0051] A fourth aspect of the present application provides an electrical device, which includes the lithium-ion battery provided by the second aspect above, or the lithium-ion battery prepared by the preparation method provided by the third aspect above.

[0052] Lithium-ion batteries can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0053] The present application will be further described below with reference to specific embodiments and comparative examples.

[0054] The positive electrode sheets, negative electrode sheets and lithium-ion batteries of Examples 1 to 14 and Comparative Examples 1 to 3 of the present application are prepared by the following method.

[0055] Positive electrode:

[0056] The positive electrode active material is mixed with the conductive agent carbon black (SP), carbon nanotubes (CNT), and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 97:1:0.5:1.5, and then added into the organic solvent N-methylpyrrolidone (NMP) and stirred at high speed to form a uniform dispersion; after the high-speed stirring, negative pressure defoaming is performed in the stirring tank to obtain a positive electrode slurry suitable for coating. The obtained positive electrode slurry is coated on aluminum foil by a transfer coater, and after drying, cold pressing, and stripping, a positive electrode sheet of the desired shape is made.

[0057] Negative plate:

[0058] (1) A negative electrode active material artificial graphite, an ether bond polymer, a conductive agent carbon black (SP), a binder styrene butadiene rubber (SBR), and an auxiliary agent carboxymethyl cellulose (CMC) are mixed in a mass ratio of (96.3-x):x:1:1.5:1.2 to obtain a mixture, and a solvent deionized water is added and stirred at a high speed to form a uniform dispersion, and then the dispersion is defoamed under negative pressure in a stirring tank to obtain a negative electrode slurry suitable for coating.

[0059] Wherein, x% is the mass percentage of the ether bond-containing polymer in the mixture.

[0060] (2) The obtained negative electrode slurry is coated on a copper foil by a transfer coater, and then coated on the other side of the copper foil after drying. After drying, cold pressing, slitting, and baking, a negative electrode sheet is obtained.

[0061] Lithium-ion battery:

[0062] The lithium ion batteries of Examples 1 to 13 were prepared by the following method.

[0063] The positive and negative electrodes are placed on both sides of the diaphragm (the diaphragm is uniformly made of polyethylene (PE) diaphragm with a thickness of 9μm, and PVDF with a thickness of 1μm is dotted on both sides) and wound to form a core, which is then hot-pressed at 90°C for 90 seconds under a pressure of 0.6MPa. The exposed parts of the positive and negative electrodes are welded to the tabs and the whole is placed in an aluminum-plastic film and pre-packaged, keeping the tabs exposed outside the aluminum-plastic film while leaving one side open. The pre-packaged battery is placed in an oven, maintained at a vacuum of -80kPa at 95°C, and baked for 9 hours. After baking, the electrolyte is injected; 10wt% of lithium hexafluorophosphate (LiPF6) is added to a mixed solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 3:5:2. 6 ), 1wt% of vinylene carbonate and 2wt% of vinyl sulfate (DTD) are used as lithium salt and additives to prepare an electrolyte; the electrolyte is injected into the aforementioned aluminum-plastic film with a core, and then a lithium-ion battery is obtained after packaging, standing and forming processes.

[0064] The preparation method of the lithium ion battery in Example 14 is substantially the same as the preparation method of Examples 1 to 13, except that the baking time of the battery after pre-packaging is adjusted from 9 hours to 6 hours.

[0065] Moisture content test of negative electrode:

[0066] The moisture tester (Mettler C30S) was preheated to 150°C and a blank sample was calibrated. Then the negative electrode sheet was taken out from the baked coil core, and a square sample with an area of ​​4cm*4cm was cut and weighed. The sample was further cut into small pieces of 0.5cm*0.5cm and placed in the sample crucible of the moisture tester. Finally, the sample mass was input and the test started.

[0067] The specific parameters of the above-mentioned Examples 1 to 14 and Comparative Examples 1 to 3 are summarized in Table 1 below.

[0068] Table 1

[0069]

[0070]

[0071] Test Case

[0072] (1) XPS test

[0073] Use a charging and discharging device to charge and discharge the battery at a current of 1 / 10 of the designed capacity ampere-hour until the voltage reaches the lower limit of the battery's operating voltage. Disassemble the battery, take out the negative electrode, soak it in dimethyl carbonate (DMC) for 3 hours, then take it out and dry it. Flatten and fix the dried negative electrode, and then test it using an XPS instrument. During the test process, you can first perform a full spectrum scan to determine the types of elements that may be present, and then perform a narrow spectrum scan for the C element.

[0074] The narrow spectrum scan focuses on the C1s signal, and the binding energy is in the range of 280-295eV. After acquiring the data, the curve needs to be separated. Since the negative electrode surface contains various C species, we use the N element as the calibration basis, and its peak position is located at 400.2eV. After adjusting the curve, the signal peak and corresponding area in the range of 282-286eV are determined. The number of signal peaks between 284 and 286eV is examined, and the test results are shown in Table 2.

[0075] There are 2 signal peaks between 282 and 286 eV, the binding energy of the first peak is 283.5 eV to 284.5 eV, the binding energy of the second peak is 284.5 eV to 285.5 eV, and the difference between the binding energy of the first peak and the binding energy of the second peak is ≤ 1 eV. Calculate the integrated area P of the first peak S1 1 and the integrated area P of the second peak S2 2 The ratio P 1 / P 2 , the test results are shown in Table 2.

[0076] like Figure 2 As shown, by comparing Example 1 and Comparative Example 1, it can be seen that, with a signal peak S6 between 290eV and 292eV and an existing signal peak between 282eV and 286eV (i.e., the second peak S2 between 284.5 and 285.5eV) as reference peaks, the C1s spectrum of the XPS test of the SEI film on the surface of the negative electrode sheet of Example 1 produces an additional signal peak between 282eV and 286eV, i.e., the first peak S1 between 283.5eV and 284.5eV, and the difference between the binding energy of the first peak and the binding energy of the second peak is ≤1eV.

[0077] (2)ICP test

[0078] The lithium-ion batteries of the above embodiments and comparative examples were cycled for 20 cycles at a rate of 0.33C within a rated voltage range (2.5 to 4.25 V for embodiments 1 to 3, 10 to 11 and comparative examples 1 and 4, 2.8 to 4.35 V for embodiments 4 to 6 and comparative example 2, and 3.0 to 4.85 V for embodiments 7 to 9 and comparative example 3) and then the state of charge (SOC) of the batteries was adjusted to 0% at a rate of 0.33C. The batteries were then tested in a glove box. Disassemble and remove the negative electrode; remove about 0.35g of graphite negative electrode powder from the coating area of ​​the electrode, add 2:6 aqua regia (the molar ratio of nitric acid and hydrochloric acid in aqua regia is 2:6) and 8ml of pure water, cover with a clean watch glass, place a graphite heating plate, and heat at 200℃ for 30min until completely dissolved; remove the sample and cool to room temperature, dilute to 100ml volumetric flask, add deionized water and shake well, and use a disposable syringe and 0.45 needle filter to take the filtrate for ICP test. The test results are shown in Table 2.

[0079] (3) Cyclic performance test

[0080] The lithium-ion batteries of the above embodiments and comparative examples are charged and discharged using a charge and discharge device at a current of 1 / 3 of the designed capacity ampere-hours to determine their actual capacity. Then, the cyclic charge and discharge operation is performed at a rate of 1C (i.e., the actual capacity ampere-hours of the battery are used as the current size) in the rated use voltage range (2.5-4.25V for embodiments 1-3, 10-11 and comparative examples 1 and 4, 2.8-4.35V for embodiments 4-6 and comparative example 2, and 3.0-4.85V for embodiments 7-9 and comparative example 3), and the number of cycles when the capacity retention rate is reduced to 80% is recorded. During the test, the lithium-ion battery is placed in a thermostat and the temperature is set to 25°C. The test results are shown in Table 2.

[0081] Table 2

[0082]

[0083] As shown in Table 2, by comparing Examples 1 to 14 with Comparative Examples 1 to 3, it can be seen that for the negative electrode sheet provided by the present application, the SEI film formed on the surface of the negative electrode active material of the negative electrode sheet during the formation process produces an additional signal peak between 282 eV and 286 eV in the C1s spectrum of the XPS test, which corresponds to the new carbon-containing species on the SEI film. The carbon-containing species inhibits the deposition of transition metal ions, improves the stability of the SEI film, and thereby improves the cycle performance of the lithium-ion battery.

[0084] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0085] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A negative electrode sheet, characterized in that: include: Anode current collector; as well as A negative electrode active material layer is arranged on the surface of at least one side of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material and a solid electrolyte interface film coated on the surface of the negative electrode active material. The solid electrolyte interface film has a C1s spectrum on the surface measured based on X-ray photoelectron spectroscopy, with at least 2 signal peaks between 282eV and 286eV, and at least 1 signal peak between 290eV and 292eV.

2. The negative electrode sheet according to claim 1, characterized in that: The solid electrolyte interface film includes one or more reaction products of a chemical reaction between an ether bond-containing polymer and a transition metal ion.

3. The negative electrode sheet according to claim 2, characterized in that: The ether bond-containing polymer includes one or more of polyethylene glycol, polypropylene glycol and polytetrahydrofuran diol; preferably, the ether bond-containing polymer includes polyethylene glycol.

4. The negative electrode sheet according to claim 1, characterized in that: The solid electrolyte interface film has a C1s spectrum on the surface measured based on X-ray photoelectron spectroscopy, and there are two signal peaks between 282eV and 286eV. The two signal peaks are a first peak and a second peak, respectively. The binding energy of the first peak is lower than the binding energy of the second peak, and the difference between the binding energy of the first peak and the binding energy of the second peak is ≤1eV.

5. The negative electrode sheet according to claim 4, characterized in that: The binding energy of the first peak is 283.5 eV to 284.5 eV, and the binding energy of the second peak is 284.5 eV to 285.5 eV; and / or, The ratio of the integrated area P1 of the first peak to the integrated area P2 of the second peak satisfies: 0.2 <P1 / P2<1。 6. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet as claimed in any one of claims 1 to 5, and a separator.

7. A method for preparing a lithium ion battery, characterized in that: The following steps are involved: The negative electrode active material, the ether bond-containing polymer, the conductive agent and the binder are mixed to obtain a mixed material, and a solvent is added to obtain a negative electrode slurry; Applying the negative electrode slurry to at least one side of the surface of the negative electrode current collector and drying it to obtain a negative electrode sheet; The positive electrode sheet, the negative electrode sheet and the separator are assembled, injected with liquid, and chemically formed to obtain a lithium ion battery.

8. The method for preparing a lithium ion battery according to claim 7, characterized in that: The water content of the negative electrode sheet is less than 300 ppm.

9. The method for preparing a lithium ion battery according to claim 7, characterized in that: The mass percentage of the ether bond-containing polymer in the mixed material is 0.3% to 0.9%.

10. An electrical device, characterized in that: It includes the lithium ion battery as claimed in claim 6, or the lithium ion battery prepared by the preparation method as claimed in any one of claims 7 to 9.